2014 11th International Joint Conference on Computer Science and Software Engineering (JCSSE) 2014
DOI: 10.1109/jcsse.2014.6841878
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised identification of malaria parasites using computer vision

Abstract: Malaria in human is a serious and fatal tropical disease. This disease results from Anopheles mosquitoes that are infected by Plasmodium species. The clinical diagnosis of malaria based on the history, symptoms and clinical findings must always be confirmed by laboratory diagnosis. Laboratory diagnosis of malaria involves identification of malaria parasite or its antigen / products in the blood of the patient. Manual diagnosis of malaria parasite by the pathologists has proven to become cumbersome. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 10 publications
0
26
0
2
Order By: Relevance
“…Nasir et al [48], used the saturation channel of image in HSI colour space and moving Knearest neighbour (MKNN) to differentiate parasite containing red blood cell. Khan et al [49] performed clustering on the 'b' component of the image converted to Lab colour space for obtaining parasite region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nasir et al [48], used the saturation channel of image in HSI colour space and moving Knearest neighbour (MKNN) to differentiate parasite containing red blood cell. Khan et al [49] performed clustering on the 'b' component of the image converted to Lab colour space for obtaining parasite region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Khan et al [6] developed a segmentation method using b* channel from the colour space of L*a*b* and KMeans to obtain the tissue of P. vivax. Nasir et al [3] used the image of P. vivax parasite as their research object, in this case, to examine the result of the classification between segmentation on the saturation channel and the intensity channel from the HIS color space.…”
Section: Related Workmentioning
confidence: 99%
“…where n refers to the maximum value of grayscale and MSE refers to Mean Square Error, a value of the average error between the image before and after processing that can be counted using Equation (6). ( 6 ) where M, N refers to the resolution of the image, g(x,y) and g ' (x,y) refers to the value before and after processing. From the Equation (5), it can be seen that PSNR is inversely proportional with MSE.…”
Section: Peak Signal To Noise Ratio (Psnr)mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, thin blood smear with Leishman stain is considered in few studies (Table 4). It is reported that Leishman stain has good sensitivity for parasite detection than Giemsa (Khan et al, 2014). Giemsa stain is much costly and also time-taking procedure than Leishman.…”
Section: Blood Smear Staining and Microscopic Imagingmentioning
confidence: 99%